Endoscopic Repair of the Proximal Hamstring - Steven F. DeFroda MD, MEng; Benjamin S. Kester MD; Alexander C. Newhouse BS; Daniel M. Wichman BS; Sunikom Suppaiksorn MD; Shane J. Nho MD, MS (SAGE Publishing, 2021)
Background: Proximal hamstring injuries are increasingly common. While open repair with suture anchors placed in the ischial tuberosity has long been the gold standard technique for surgical management, endoscopic techniques can allow for smaller incisions, reduced wound complications, and an expedited recovery. Indications: Patients with full-thickness 3-tendon proximal hamstring tears, 2-tendon tears with retraction >2 cm, or partial tears that remain symptomatic despite conservative management are considered for surgery. High-demand patients are often treated acutely, and low-demand patients may be offered surgery after a conservative management period. Technique Description: In the prone position, 2 arthroscopic portals are created in the gluteal fold. Fluoroscopy is used to verify safe portal placement, and the sciatic nerve is visualized along with the retracted tendon origin. The ischial tuberosity is identified, and the hamstring origin is debrided and decorticated. An accessory portal is created for suture anchor placement. Two double-loaded anchors are placed in the tuberosity, the sutures of which are used to repair the hamstring tendons using a horizontal mattress configuration. Patients undergo a stepwise postoperative physical therapy protocol. Results: An 85% return to sport rate can be expected following all hamstring repairs, with some studies reporting as high as 95% after endoscopic repair. Compared with nonoperative treatment, proximal hamstring repair overall results in higher patient satisfaction and return to sport. While large studies have yet to report on outcomes compared with the traditional open technique, the smaller incisions look to reduce wound complications and postoperative pain. Discussion/Conclusion: Recent advancements in endoscopic techniques have allowed for adequate visualization and robust repair of proximal hamstring avulsions. We present our endoscopic technique of the proximal hamstring, which, compared with the traditional open repair, can decrease perioperative complications and accelerate recovery.